2015
DOI: 10.1136/tobaccocontrol-2014-052073
|View full text |Cite
|
Sign up to set email alerts
|

Standardised packaging and new enlarged graphic health warnings for tobacco products in Australia—legislative requirements and implementation of theTobacco Plain Packaging Act 2011and theCompetition and Consumer (Tobacco) Information Standard,2011

Abstract: This paper describes the development, content and implementation of two pieces of Australian tobacco control legislation: one to standardise the packaging of tobacco products and the other to introduce new, enlarged graphic health warnings. It describes the process of legislative drafting, public consultation and parliamentary consideration. It summarises exactly how tobacco products have been required to look since late 2012. Finally, it describes implementation, most particularly, the extent to which packs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 7 publications
2
40
0
Order By: Relevance
“…This assertion exists despite the obvious logic that one cannot prove the effectiveness of something until it is implemented. Moreover, recent analysis has demonstrated that the industry-sponsored research to demonstrate the ineffectiveness of plain packaging legislation is methodologically weak (Hatchard, Fooks, Evans-Reeves, Ulucanlar, & Gilmore, 2014; Laverty, Diethelm, Hopkinson, Watt, & McKee, 2015; Ulucanlar, Fooks, Hatchard, & Gilmore, 2014), while suggesting that the legislation in Australia (the first country to implement this measure) is indeed having the intended effect (Scollo, Lindorff, Coomber, Bayly, & Wakefield, 2015; Wakefield, Hayes, Durkin, & Borland, 2013). Experimental studies have also supported the effectiveness of plain packaging legislation (Hammond, 2010; Hammond, Daniel, & White, 2013; Thrasher, Rousu, Hammond, Navarro, & Corrigan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This assertion exists despite the obvious logic that one cannot prove the effectiveness of something until it is implemented. Moreover, recent analysis has demonstrated that the industry-sponsored research to demonstrate the ineffectiveness of plain packaging legislation is methodologically weak (Hatchard, Fooks, Evans-Reeves, Ulucanlar, & Gilmore, 2014; Laverty, Diethelm, Hopkinson, Watt, & McKee, 2015; Ulucanlar, Fooks, Hatchard, & Gilmore, 2014), while suggesting that the legislation in Australia (the first country to implement this measure) is indeed having the intended effect (Scollo, Lindorff, Coomber, Bayly, & Wakefield, 2015; Wakefield, Hayes, Durkin, & Borland, 2013). Experimental studies have also supported the effectiveness of plain packaging legislation (Hammond, 2010; Hammond, Daniel, & White, 2013; Thrasher, Rousu, Hammond, Navarro, & Corrigan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3 The same source indicates that in November 2012 more than half of the packs of cigarettes sold were in plain packaging. Furthermore, Quitline statistics indicate that the number of calls to the Quitline rapidly increased after 1 October 2012 to peak in November 24 .…”
Section: Plain Packagingmentioning
confidence: 99%
“…Among the proposed measures, Parties are invited "to restrict or prohibit the use of logos, colours, brand images or promotional information on packaging other than brand names and product names displayed in a standard colour and font style." 1 Australia was the first country to introduce this proposal by adopting the Tobacco Plain Packaging Act in November 2011 with progressive implementation between 1st October and 1st December 2012 2,3 . The objectives of the plain (or standardized) packaging measure are to: "(a) reduce the appeal of tobacco products to consumers; and (b) increase the effectiveness of health warnings on the retail packaging of tobacco products; and (c) reduce the ability of the retail packaging of tobacco products to mislead consumers about the harmful effects of smoking or using tobacco products."…”
Section: Introductionmentioning
confidence: 99%
“…Past studies occurred using fully branded packs and cigarette sticks and so needed to obscure markings on the cigarette stick which might identify the brand, either by blindfolding participants22 or by covering the cigarette rod with a label,24 either of which could themselves influence taste ratings. Under the Tobacco Plain Packaging Act 2011,53 the appearance of cigarette sticks has been standardised to a white paper casing or white with a cork tip and with brand names and decorative features removed from the stick 1. This created a unique opportunity to use unmodified, commercially available products.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of plain packaging in Australia removed all imagery, colours and symbols from cigarette packs, requiring all packs to be sold in drab dark brown packaging with standardised appearance and positioning of brand and variant names 1. There is increasing evidence from naturalistic and post-implementation studies that plain packaging negatively impacts the enjoyment, quality and satisfaction of cigarettes when they are smoked 2–6.…”
Section: Introductionmentioning
confidence: 99%